Politics in black and white : race and power in Los Angeles - Sonenshein, Raphael (Princeton University Press, 1993)
This book reaches deep into the past of the city of Los Angeles and carries through to the dramatic events that have recently received global attention - the Rodney King beating and the uprising in South Central L.A. Tracing the evolution of an extraordinary biracial coalition in Los Angeles behind African-American Mayor Tom Bradley, Raphael Sonenshein shows how "crossover" politics and racial violence coexist in the paradoxical world of urban America. In this first book-length examination of the politics of the second largest (and possibly the most) diverse city in the United States, Sonenshein reveals the surprising durability of the political linkage between Blacks and white liberals, particularly Jews. This coalition also offered a major role to the business community, and expanded to include Latinos and Asian-Americans. The author combines interviews, original voting analyses, and a wide array of archival sources to explore coalition patterns at the elite and mass levels. While challenging the prevailing pessimism about biracial coalitions in general, he also compares their relative successes in Los Angeles to their disheartening failures in New York City. What emerges is a probing look at a crucial issue of politics in the United States: can whites, African-Americans, Latinos, Asian-Americans, and other minorities find common ground?